Two decades of the Journal of Intellectual Capital: a bibliometric overview and an agenda for future research - Dabić, Marina (2022)
Purpose: The Journal of Intellectual Capital (JIC) is one of the leading academic journals in the field of business and management, with an impact factor of 3.744, according to Journal Citation Reports from Clarivate Analytics, 2019. This study reports the results of a content analysis of the JIC articles that have been published since the journal was founded in 2000, in order to highlight its significant contribution and identify potential future research avenues within the business and management field. Design/methodology/approach: Scopus database, complemented by the Web of Science (WOS) Core Collection, was used. Furthermore, this study graphically maps over 20 years' worth of bibliographic material, using the visualization of similarities (VOS) to present an overview of the journal and identify future research avenues. Findings: The paper provides an overview of a total of 700 articles and editorial notes, authored by leading authors from various universities, as well as collating the research themes explored during the 20 year period between 2000 and 2019. The prestigious positioning of this journal is evidenced both through the increasing number of citations received from other highly regarded journals and through its impact upon the establishment of new streams of research. Practical implications: By applying a bibliometric analysis, this paper offers an overview of past and current themes on intellectual capital (IC). Originality/value: This article delivers an in-depth and rigorous analysis of the fields and research streams interrogated by the JIC over the last 20 years and offers potential topics for future research, which could stimulate authors and inspire advancements in research for years to come.